THE CONCEPT OF POLITICAL PEOPLE IN THE BRAZILIAN REGENCY: REVOLUTION AND THE LANGUAGE POLICY HISTORICIZING (1831-1840) - Rauter Pereira, Luisa (Revista de Historia Social y de las Mentalidades, 2024)
The article analyses the history of the political  concept of people in political debate during  the Regency period in Brazilian history  (1831-1840) through a theoretical perspective  that seeks to understand how language and  political thinking becomes historicized as  a characteristic of modernity. Thus, the  paper traces the incorporation of historical  temporality in conceptual semantics, a  phenomenon that occurred in the midst of  conflicts and political debates during the  formation and consolidation of the Brazilian  Imperial State. The concept of people was  historicized then unveiling its contingency,  that is, its definition based on the analyses of  present historical situation, and processual  and futuristic visions of history as well.  These new uses and meanings of the concept  opposed to the theoretical concept of people  used by liberal groups during the 7th of April  Revolution (1831).
Keywords: history of political concepts; temporality; people; Brazilian political debate; Imperial Brazil